A Systems improvement study on ABENSON's Sales Corp. - Amis, Monnaliz; Balucan, John Paul; Seriña, Carmela Patricia; Sanchez, Richard Paul (College of Engineering, 2003)
Retailing, according to Webster dates back to the 14th century, means the selling of goods to ultimate consumers for personal or household consumption. In the Philippines, retailing has been around for over 30 years now and much advancement has been seen. Today, everywhere you go retailers of different types of goods can be found. These companies would sell from bags, shoes to televisions and washing machines. ABENSON is a retailer of consumer electronics. It started as an appliance store in 1970 pioneering the concept of supermarketing appliances under one roof. Today, ABENSON has grown into being the country?s biggest retail network of offices and stores, each catering to specific markets and industries. ABENSON is part of the Benison Group of companies with the vision of innovation, growth, leadership, service and responsibility towards customer satisfaction. In line with this vision, the company continually thrives to improve its services to better serve its customers. In this regard, the company consulted with the Department of Industrial Engineering and Operations Research to do a project study and analyze their operations for better efficiency and customer service because ABENSON C.A.R.E.S.